2015
DOI: 10.1038/ncomms9865
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid-dependent cell entry of human enterovirus D68

Abstract: Human enterovirus D68 (EV-D68) is a causative agent of childhood respiratory diseases and has now emerged as a global public health threat. Nevertheless, knowledge of the tissue tropism and pathogenesis of EV-D68 has been hindered by a lack of studies on the receptor-mediated EV-D68 entry into host cells. Here we demonstrate that cell surface sialic acid is essential for EV-D68 to bind to and infect susceptible cells. Crystal structures of EV-D68 in complex with sialylated glycan receptor analogues show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
138
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(154 citation statements)
references
References 56 publications
10
138
0
6
Order By: Relevance
“…Using knockout cell lines and gene reconstitution, we have shown that EV-D68 can use both α2,6-and α2,3-linked Sia as a receptor to infect cells. This finding extends recent observations that both α2,6-and α2,3-linked Sia-containing trisaccharides can bind to the EV-D68 capsid and initiate virion uncoating in vitro (26). The observation that EV-D68 can use not only α2,6-linked Sia as a receptor but also α2,3-linked Sia, which resides mainly in the lower respiratory tract, may provide an explanation for its ability to cause severe lower respiratory tract infections.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Using knockout cell lines and gene reconstitution, we have shown that EV-D68 can use both α2,6-and α2,3-linked Sia as a receptor to infect cells. This finding extends recent observations that both α2,6-and α2,3-linked Sia-containing trisaccharides can bind to the EV-D68 capsid and initiate virion uncoating in vitro (26). The observation that EV-D68 can use not only α2,6-linked Sia as a receptor but also α2,3-linked Sia, which resides mainly in the lower respiratory tract, may provide an explanation for its ability to cause severe lower respiratory tract infections.…”
Section: Discussionsupporting
confidence: 86%
“…4 and Tables S1 and S2). Although residues that differed between Siadependent and -independent strains in clade A show little overlap with those that were altered in clade B, some of the changed residues on the viral surface are near the Sia-binding site (26) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their structural study of rhinovirus C, Liu et al (1) examine the shape of the canyon (14), a pocket at the base of the protruding spikes on the surface of the rhinovirus capsid. A similar location on the enterovirus D68, a related virus also associated with severe disease in children, had previously been shown to interact with sialylated cadherin-related family member 3 (CDHR3) (15). Whereas other rhinoviruses have flat plateaus and wide canyons in their capsid surface, the rhinovirus C surface canyons more closely resemble the surface canyons of enterovirus D68; a closer look at the canyons (Fig.…”
mentioning
confidence: 61%
“…The canyon allows only limited access to these antibodies (22). In many EVs, a hydrophobic pocket within the VP1 jelly roll and situated underneath the canyon floor is occupied by a fatty-acid like molecule, or "pocket factor" (23,24), that regulates the conformational states of the virus during cell entry (25). Capsidbinding reagents that replace the pocket factor within VP1 are effective antiviral therapeutics against many EVs (26), but not RV-Cs (14).…”
mentioning
confidence: 99%